DO FUNDEF AO FUNDEB: O QUE MUDA PARA O FINANCIAMENTO DA EDUCAÇÃO MUNICIPAL? - Silvio Cesar Nunes Militão (Universidade do Oeste Paulista, 2010)
Related to a larger research, this article main purpose was analyzing how the recent substitution of FUNDEF for FUNDEB may favor the municipal effort in supporting the school levels put under its responsibility. Documental and bibliographical studies were used as research procedures, starting with a comparison between both Funds proposals in order to reveal current advances and limits as far as children education financial support is concerned as well as young and adult education. The results have shown that FUNDEB represented an enormous step ahead if compared with previous situation, allowing the return of municipality investment in school levels under its responsibility. Nevertheless, they have also pointed the low income destined to children education and also young and adult education as an obstacle to be overcome.